HEALTH AND SPIRITUALITY DALAM PENGEMBANGAN WELLNESS TOURISM BERBASIS KEPADA MASYARAKAT DI DESA WISATA KENDERAN KABUPATEN GIANYAR - Putu Herny Susanti; Gusti Alit Suputra; Wina Premayani; I.A. Indriani (Fakultas Pariwisata Universitas Pancasila, 2023)
Several areas in Bali have the potential to develop wellness tourism, namely from their natural resources, one of which is the Kenderan Tourism Village, Gianyar Regency. Kenderan Tourism Village can develop into a wellness tourism attraction by utilizing its natural resources. The purpose of this study was to formulate health and spiritual strategies and programs in the development of community-based wellness tourism in Kenderan Tourism Village. Theory of change as a grand theory, research uses qualitative methods supported by Interpretive Structural Modeling (ISM) analysis. Completion of the ISM questionnaire through the Expert Survey involved seven experts to obtain information regarding contextual relationships in each element and sub-element in the questionnaire. From the results of the analysis the following strategies can be obtained: Increasing the role of the community, local entrepreneurs and the government through good cooperation in the development of wellness tourism; Increasing the competence of local human resources in the development of wellness tourism; Increasing the role of the Regional Government of Gianyar Regency in the development of wellness tourism; Increasing the role of Pokdarwis in managing wellness tourism in the Kenderan Tourism Village; Increasing the role of academics in tertiary institutions is related to research and development of HR competencies, especially in the field of wellness tourism.